Flash Cache Hybrid Storage System For Video-On-Demand Server - Al-Wasabi, Ola Ahmed Mohammed (2018)
A video-on-demand (VOD) system allows users to access any video at any time. This system enables users to view videos in the real-time streaming mode for extended durations. One of the important components of the VOD systems is the hybrid storage server. This component consists of HDD, SSD, and RAM, collectively fulfilling the requirement of simultaneous fast data access and large data distribution to numerous users. However, current hybrid storage systems still pose numerous challenges. (1) The integration and roles of the HDD, SSD, and RAM are relatively weak in terms of optimizing fast access prior to streaming to a large number of simultaneous users. (2) The HDD and SSD exhibit poor data layout and streaming controller in supporting the production of a high number of simultaneous streams. This thesis proposes (1) an enhanced hybrid storage system (EHSS) for the VOD servers. The HDD, SSD, and RAM are managed and integrated using an effective mechanism, in which the top 10% most popular videos are utilized to achieve fast data access and service to a large number of simultaneous users. (2) The flash cache hybrid storage system (FCHSS) is also proposed. Unlike the EHSS architecture, the FCHSS architecture has no RAM, which is removed and replaced by a flash-based SSD. The flash-based SSD is used instead of the RAM as a cache for the HDD to achieve fast data access and service to a large number of simultaneous users. (3) The new data layout stores thousands of video segments in the HDD and SSD.